2015
DOI: 10.1007/s10823-015-9270-0
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving in Dementia and its Impact on Psychological Functioning and Health-Related Quality of Life: Findings from a Colombian Sample

Abstract: Existing published studies about health-related quality of life (HRQOL) in caregivers of dementia patients living in Latin American countries are very limited. However, cultural aspects, personal values, and social structure may affect the way caregivers experience their role in different societies. The current study investigated the relationship between HRQOL and psychological factors using a cross-sectional design. The sample consisted of 102 informal caregivers of patients with dementia from Bogotá, Colombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 77 publications
3
18
0
2
Order By: Relevance
“…After adjusting for socio-demographic variables and FIS scores, those with depressive symptoms were significantly associated with lower QOL across all four domains of physical health, psychological, social relationships and environment while those with symptoms of anxiety were only significantly associated with low social relationships domain. This was in line with Moreno et al who found significant correlations between caregivers’ mental health and QOL among informal caregivers of patients with dementia in Colombia [46]. In particular, caregivers with higher levels of self-reported depressive symptoms reported lower vitality and worse general health (health related QOL as measured by the SF-36).…”
Section: Discussionsupporting
confidence: 88%
“…After adjusting for socio-demographic variables and FIS scores, those with depressive symptoms were significantly associated with lower QOL across all four domains of physical health, psychological, social relationships and environment while those with symptoms of anxiety were only significantly associated with low social relationships domain. This was in line with Moreno et al who found significant correlations between caregivers’ mental health and QOL among informal caregivers of patients with dementia in Colombia [46]. In particular, caregivers with higher levels of self-reported depressive symptoms reported lower vitality and worse general health (health related QOL as measured by the SF-36).…”
Section: Discussionsupporting
confidence: 88%
“…Caregivers with high life satisfaction scores scored lower for depression than dissatisfied life individuals. This finding is consistent with findings in literature, as verified by a study by Moreno et al 13 Among the 102 caregivers evaluated, those who scored high for depression scored low for life satisfaction. Hansen and Slagsvold 8 evaluated 2,553 caregivers of spouses and reported similar data.…”
Section: Discussionsupporting
confidence: 92%
“…Life satisfaction is significantly associated with depressive symptoms, as shown by a study conducted by Moreno et al 13 . Caregivers with the greatest risk of developing depression are those who score lower for life satisfaction.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Another qualitative study reports the strategies that lesbian caregivers of an individual with dementia used to negotiate family issues in the context of their caregiving experience (Price, 2011). Universally, family caregivers of individuals with dementia are mainly women (Moreno et al, 2015). Surprisingly, the experience of lesbian family caregivers is seldom addressed and their contributions largely overlooked under the heterosexist lens.…”
Section: Dementia/hiv-related Dementiamentioning
confidence: 99%